Potential Determinants of Regional Variation of Three American Aroma Hops Grown in the Willamette Valley, Oregon. (6th October 2022) - Van Simaeys, Karli R.; Féchir, Michael; Gallagher, Andy; Stokholm, Arnbjørn; Weaver, Garrett; Shellhammer, Thomas H.
Abstract: The influence of growing region on hop quality was examined in three American aroma hop varieties (Mosaic®, Simcoe® and Strata®) that were harvested from two to five distinct sites within each of eleven commercial fields located throughout the Willamette Valley, Oregon. Weather, climate, and management data were collected for each of the eleven fields, while site-specific soil characterization was performed at each of the 50 sites. While hop variety had the largest influence on chemical differences, Multiple Factor Analysis revealed regional groupings attributable to differences in soil, weather, and management. Supplemental data for this article is available online at at https://doi.org/10.1080/03610470.2021.1968272 .